Upaya Meningkatkan Kinerja Petugas Pasasi Melalui Disiplin Kerja pada Karyawan PT. Kokapura Avia Cabang Bandar Udara Internasional Yogyakarta - Maria Agata Matwaan; Sri Sutarwati (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
ABSTRACT, PT Kokapura Avia Yogyakarta International Airport Branch serves ground handling services for air transportation companies. This research is focused on Ground Handling services for pasasi officers, namely check-in, boarding and lost and found. The problem in this study is related to the lack of work discipline of pasasi officers seen in carrying out their duties or work. This study aims to determine the work discipline carried out in an effort to improve the performance of pasasi officers to determine the work discipline that should be carried out in the future in an effort to improve the performance of pasasi officers of PT Kokapura Avia Yogyakarta International Airport Branch. This research uses qualitative research methods. The subjects in this study were the head (leader) and the passation officer of PT Kokapura Avia Yogyakarta International Airport Branch. The data used in this study were obtained from observations, interviews and documentation. Data analysis used in this research is data reduction, data presentation, conclusion drawing and data verification. The results of this study indicate that the work discipline carried out in an effort to improve the performance of pasasi officers is entering work on time, doing work in accordance with company regulations and supervision by the leader. Requiring employees to obey all applicable regulations at PT Kokapura Avia Yogyakarta International Airport Branch in order to improve employee performance. Work discipline that should be carried out in the future in an effort to improve the performance of pasasi officers is that leaders must be more assertive in making decisions and providing sanctions or reprimands for employees who are not disciplined at work. In addition, it is necessary to increase wages and salaries for employees whose performance is good so that it will encourage other employees to improve their performance.